Digging up the Past : Adventures of Wishbone #6 - Sathre, Vivian; Irving, Washington, 1783-1859. (Milwaukee, WI : Gareth Stevens Pub., 1999)
Because Wishbone keeps getting interrupted while trying to take a nap, he begins thinking about Rip Van Winkle and finds himself in Rip's shoes, finally waking to a changed world.
Originally published: Allen, Tex. : Big Red Chair Books, c1997. (The adventures of Wishbone ; #6)
Keywords: Dogs -- Fiction; Time travel -- Fiction; Catskill Mountain Region (N.Y.) -- Fiction